Digital Humanities and Distributed Cognition: From a Lack of Theory to its Visual Augmentation - Florian Windhager; Eva Mayr (Journal of Cultural Analytics)
Digital humanists have often been criticized as too technology-driven and for a lack of theoretical work. In this paper, we discuss theories from Cognitive Science on the *extended mind*, which provide a productive framework to theorize the use of tools and technologies for the sake of cognitive self-enhancement. Viewed through this lens, humans continuously self-amplify their natural cognitive resources and processes by extending and offloading them to interactions with artifacts and other individuals in their environment. Concepts of extended cognition further sharpen the focus on multiple types of distribution: from the outlined internal-external distribution to the propositional-visual distribution of cognition, but also for the multi-instrumental distribution across multiple types of tools and tool specialist. All these aspects are relevant for future debates about a "theory gap" in the digital humanities: DH mainly builds external, technological tools, while traditional humanities develop conceptual tools---including theories---to enable and enhance the study of complex cultural phenomena. Notwithstanding the value of confrontational discussions, we argue for the benefits of understanding the strengths and limitations of instruments on both sides---and for working toward future synergies and ecologies of the humanities' tools and minds. In this regard, we show how visualization-based DH tools might might play a major role in closing the comprehensibility gap of traditional theories in the arts and humanities.